Time-Inconsistent Generosity: Present Bias across Individual and Social Contexts - Felix Kölle; Lukas Wenner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
We investigate the presence and stability of dynamically inconsistent time preferences across contexts with and without interpersonal trade-offs. In a longitudinal experiment subjects make a series of intertemporal allocation decisions of real-effort tasks between themselves and another person. We find substantial time inconsistency in generosity: agents become disproportionally more selfish when decisions have immediate rather than delayed consequences. Based on our theoretical framework, structural estimations reveal that this is because agents exhibit present bias in own but not in others' consumption. We show that very similar differences in present bias are observed in the absence of any interpersonal trade-offs, when agents decide either for themselves or on behalf of another person. At the individual level, we find that present bias in own consumption is a stable behavioral trait which is correlated across individual and social contexts.
Keywords: C91; D64; D90; 330; Present bias; altruism; stability; real effort; dictator game; intertemporal choice